Synthesis and Thermal Stability of Some Unsaturated Polyamides - Patel, D.S.; Bharambe, Y.M.; Patel, R.M. (Asian Journal of Chemistry, 2010)
Unsaturated resins were prepared by condensing β-(2-methoxy-5-methylphenyl) glutaconic acid (2MMPGA) with various diacetates. Theses resins were characterized by IR spectroscopy, vapour pressure osmometry, thermogravimetric analysis, differential scanning calorimetry and elemental analysis. The kinetics of decomposition of these resins were studied. The kinetic parameters were determined by the Broido method. The results indicated that the resins possess good thermal stability.